Phase space quantization and loop quantum cosmology: A Wigner function for the Bohr-compactified real line - Sahlmann, Hanno; Fewster, Christopher (Classical and Quantum Gravity, 2008)
We give a definition for the Wigner function for quantum mechanics on the Bohr compactification of the real line and prove a number of simple consequences of this definition. We then discuss how this formalism can be applied to loop quantum cosmology. As an example, we use the Wigner function to give a new quantization of an important building block of the Hamiltonian constraint. © 2008 IOP Publishing Ltd.